Buried Interface Regulation with TbCl3 for Highly-Efficient All-Inorganic Perovskite/Silicon Tandem Solar Cells - Chai, Wenming; Zhu, Weidong; Xi, He; Chen, Dazheng; Dong, Hang; Zhou, Long; You, Hailong; Zhang, Jincheng; Zhang, Chunfu; Zhu, Chunxiang; Hao, Yue (Nano-Micro Letters, 2025)
All-inorganic perovskite materials exhibit exceptional thermal stability and promising candidates for tandem devices, while their application is still in the initial stage. Here, a metal halide doping strategy was implemented to enhance device performance and stability for inverted CsPbI3 perovskite solar cells (PSCs), which are ideal for integration into perovskite/silicon tandem solar cells. The lanthanide compound terbium chloride (TbCl3) was employed to improve buried interface between [4-(3,6-Dimethyl-9H-carbazol-9-yl) butyl] phosphonic acid (Me-4PACz) and perovskite layer, thereby enhancing the crystallinity of CsPbI3 films and passivating non-radiative recombination defects. Thus, the inverted CsPbI3 PSCs achieved an efficiency of 18.68% and demonstrated excellent stability against water and oxygen. Meanwhile, remarkable efficiencies of 29.40% and 25.44% were, respectively, achieved in four-terminal (4T) and two-terminal (2T) perovskite/silicon mechanically tandem devices, which are higher efficiencies among reported all-inorganic perovskite-based tandem solar cells. This study presents a novel approach for fabricating highly efficient and stable inverted all-inorganic PSCs and perovskite/silicon tandem solar cells. Highlights: 1 The lanthanide compound of TbCl3 improved the wettability of Me-4PACz and further enhanced crystallization, in which the additional Cl− ions passivate iodine vacancy and improve energy level alignment at buried interface. 2 The inverted CsPbI3 PSCs with TbCl3 achieved a remarkable efficiency of 18.68% and enhanced stability in ambient air. 3 Efficiencies of 29.40% and 25.44% were, respectively, achieved in 4T and 2T all-inorganic perovskite/silicon mechanically tandem devices.